Familial Polyposis Coli: The Management of Desmoid Tumor Bleeding - Calogero, Armando (Open Med (Wars), 2019)
BACKGROUND: There is currently no standard treatment for desmoid tumors (DTs) associated with familial polyposis coli (FAP). Familial adenomatous polyposis in DT patients is sometimes a life-threatening condition. METHODS: We enrolled all consecutive patients with FAP treated at Unit of General Surgery and Transplant, University of Naples Federico II and evaluated the incidence of DTs on FAP between 1996 and 2016. RESULTS: We observed 45 consecutive patients with FAP; of these 5 were DT-FAP-associated. All 5 cases with FAP were young women, age 25 to 65 years, previously treated by colectomy. Of these, 4 patients presented a parietal localization and had been treated with a wide surgical exeresis; one patient had an intra-abdominal, mesenteric tumor that was unresectable at laparotomy. We performed CT-guided drainage, ureteral stenting, medical therapy (sulindac+tamoxifene), and chemotherapy (dacarba-zine+doxorubicine). All patients were alive and underwent follow-ups for 5 years post-surgery; only 1 patient with parietal localization showed a local relapse after 2 years. CONCLUSIONS: We propose a modulated approach to the single patient with FAP, with surgery as treatment of choice for parietal localization disease and integrating different kinds of therapies (surgery alone or associated with RT, CT) for the intra-abdominal tumor.